2017
DOI: 10.1144/sp456.8
|View full text |Cite
|
Sign up to set email alerts
|

Tsunami landfalls in the Maltese archipelago: reconciling the historical record with geomorphological evidence

Abstract: The Maltese Islands lie in the middle of the tsunamigenic Mediterranean domain, around whose margins and islands evidence of historic tsunami landfall has been increasingly recognized in recent years. Critical review of historical evidence of events in 1693 and 1908 indicates extremely modest tsunami impacts. In marked contrast, though, recently discovered geomorphological evidence summarized herein suggests that Malta's coastlines have been overwashed up to elevations of >20 m asl by an exceptional event. A n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…Calleja 2010) or pluvial storm flooding (Malta Resources Authority 2013) or is focused on the evidence for extreme events in the past: their causes; processes of initiation and their impacts. This has included work on past tsunamis (Biolchi et al 2016;Causon Deguara and Gauci 2017;Mottershead et al 2018) and geomorphological phenomena including landslides, rock fall, sea-arch collapses and dolines (Mantovani et al 2013;Prampolini et al 2018;Satariano and Gauci 2019;Devoto et al 2021). Recent research has not only criticised the catalogue of, and policies associated with, pluvial storm flooding, but has also highlighted that Malta is exposed to a much wider range of environmental extremes than has been commonly supposed (Jones 2018;Main et al 2018;Main 2019) In this paper and accompanying supplementary material (Table S1) we publish Malta's first multi-hazard historical catalogue in which geophysical, geomorphological and meteorological extremes are recorded, identified and in some cases inferred, from the Miocene epoch (c. 23-c. 25 Ma) to 2019 CE.…”
Section: Maltamentioning
confidence: 99%
See 1 more Smart Citation
“…Calleja 2010) or pluvial storm flooding (Malta Resources Authority 2013) or is focused on the evidence for extreme events in the past: their causes; processes of initiation and their impacts. This has included work on past tsunamis (Biolchi et al 2016;Causon Deguara and Gauci 2017;Mottershead et al 2018) and geomorphological phenomena including landslides, rock fall, sea-arch collapses and dolines (Mantovani et al 2013;Prampolini et al 2018;Satariano and Gauci 2019;Devoto et al 2021). Recent research has not only criticised the catalogue of, and policies associated with, pluvial storm flooding, but has also highlighted that Malta is exposed to a much wider range of environmental extremes than has been commonly supposed (Jones 2018;Main et al 2018;Main 2019) In this paper and accompanying supplementary material (Table S1) we publish Malta's first multi-hazard historical catalogue in which geophysical, geomorphological and meteorological extremes are recorded, identified and in some cases inferred, from the Miocene epoch (c. 23-c. 25 Ma) to 2019 CE.…”
Section: Maltamentioning
confidence: 99%
“…8,000 years BP, 21 July 365 CE, 4 February 1169 and 20 February 1743, impacted the coastline of the archipelago(Pareschi et al 2006;Pararas-Carayannis 2011;Biolchi et al 2016;Mottershead et al 2018;Main 2019). Conversely, the use of historical texts in relation to meteorological and geomorphological phenomena must be treated with caution as they often lack a temporal framework required for event identification and inclusion within the catalogue.…”
mentioning
confidence: 99%
“…A recent review of possible origins for boulder deposits by Dewey et al (2021) identified five marine and non-marine mechanisms that might be responsible for their occurrence along shorelines. Of these, boulder deposits attributable to high-energy wave (HEW) action have been found in a variety of coastal settings, such as submarine forereef slopes (Etienne, 2012), beaches (Lau et al, 2015), rocky shorelines (Jones and Hunter, 1992;Paris et al, 2011), coral reef platforms (Nott, 1997;Terry et al, 2013), elevated terraces (Sussmilch, 1912;Ota et al, 2015;Mottershead et al, 2017), and cliff tops (Williams and Hall, 2004;Hall et al, 2006;Roig-Munar et al, 2018). It is understood that considerable energy is required for clast production by waves, i.e.…”
Section: Introduction Wave-transported Bouldersmentioning
confidence: 99%
“…Beyond tropical waters, the presence of non‐reef‐derived boulders along coastlines is also providing evidence of past HEW events, either in the context of storm or tsunami research (Cox et al ., ; Paris et al ., ; Mottershead et al ., ; Mottershead et al ., ; Salzmann & Green, ). Some non‐carbonate boulders can be dated using different techniques to their carbonate counterparts, but corroborating evidence is often needed to establish a chronology (Goff et al ., ).…”
Section: Introductionmentioning
confidence: 99%